Analysis of air pollutant distribution at the incinerator hazardous waste treatment facility in Nambo Village, Regency of Bogor - Dody Choeruddin; Sutanto; Rosadi (Indonesian Journal of Applied Environmental Studies, 2025)
The population of Indonesia continues to grow every year, resulting in an increasing number of industries to meet the needs of daily life. The growth in the number of industries reflects the progress of national economic development. However, industrial activities, in addition to generating positive impacts on economic growth, also produce negative impacts on the environment. The generation of Hazardous and Toxic Waste (B3 waste) is one of the negative consequences of industrial activities which, if not properly managed, can pose serious risks to the environment, human health, and the sustainability of the industrial activities themselves. One of the available options for managing B3 waste is treatment using incinerator technology. This study was conducted with the objective of determining and analyzing the concentrations of air pollutants in both emissions and ambient air, as well as the spatial distribution of air pollutants, specifically SO₂, NO₂, and Total Suspended Particulate (TSP), released from the incinerator chimney that have the potential to pollute the environment surrounding the company’s operational area, by comparing the results with baseline data used during the preparation of the Environmental Impact Assessment (AMDAL). This study employed a quantitative analytical approach using the concepts of classification, calculation, measurement, and causal relationship analysis to address the research questions. Meteorological data were utilized, including wind rose analysis, atmospheric stability classification, determination of receptor points, and analysis of wind speed profiles, which were processed using WRPlot software. Furthermore, dispersion patterns were interpreted and visualized using Surfer software to identify pollutant dispersion characteristics. The results of the study indicate that the distribution of SO₂, NO₂, and TSP pollutants does not cause pollution in the surrounding environment, and the measured concentrations remain below the government-established ambient air quality standards and are consistent with the analysis data used during the AMDAL preparation. The scope of the measurements was limited to the distribution of air pollutants around the company’s operational area in accordance with the AMDAL document, and the measured parameters were key air quality indicators referring to Government Regulation No. 22 of 2021, Appendix VII, namely SO₂, NO₂, and TSP.